ANALISIS KUALITAS PERAIRAN DI SUNGAI KOMERING DESA ULAK JERMUN KABUPATEN OGAN KOMERING ILIR SEBAGAI DASAR PENGELOLAAN BUDIDAYA IKAN SISTEM KERAMBA - Reno Irawan; Robiyanto Hendro Susanto; Mohamad Rasyid Ridho (Universitas Sriwijaya, 2017)
ABSTRACT The increasing of people amount, the more activities done happen around the Komering River. Many activities done can potentially lead to a decrease in water quality in the river. This study aimed to analyze the water quality in accordance with the raw river water quality criteria for class I and to analyze the water quality state in the Komering river of Ulak Jermun village Sirah Pulau Padang District. This research was conducted in the Komering Ulak Jermun village Sirah Pulau Padang District from November to December 2016. The observation of water samples conducted at the Laboratory Pengujian Terpadu of Chemistry Faculty of Mathematics University of Sriwijaya. This research used survey method that consists of three stations with 9 sampling points and sampling was conducted 4 times in a month. Based on the analysis of water quality parameters are still within the range of quality standards among others, temperature, pH, BOD5 and phosphate while the water quality parameters exceed the quality standard that TSS, dissolved oxygen, COD and ammonia and based on the analysis storet Komering river waters classified into water quality class C, i.e. moderately contaminated. Keywords: Komering River, Water Quality, Storet Methods, Water Quality Index